Envirosense Nexus: IoT-Driven Precision Waste Management for Urban Sustainability - Syed Touseef Ali; Basavaraj Kawdi (International Journal of Robotics and Automation in Mechanics, 2024)
In modern urban environments, the improper handling of waste has become a significant issue, particularly due to insufficient and inefficient management of trash collection. This growing problem is leading to unhygienic conditions and pollution, requiring the introduction of smart waste disposal systems. To address this, we propose the development of an Internet of Things (IoT)-based intelligent trash bin that can autonomously detect, monitor, and report its waste levels. The system is being designed to automatically open its lid when someone approaches to deposit waste, and it will close afterward to ensure proper hygiene and reduce odor. Our study of this smart waste container is equipped with sensors that continuously track the volume of trash inside and provide real-time information about its status. When the waste reaches a predefined capacity, the system will notify the responsible personnel through a wireless communication system. Utilizing GSM technology, the bin can send notifications in the form of text messages to alert the designated user, ensuring timely emptying and maintenance. This web interface offers a real-time overview of bin statuses, accessible from anywhere, and provides an efficient way to manage waste collection operations. Overall, our research will enhance cleanliness in public spaces, reduce waste overflow, and support the development of smarter, more sustainable cities.
Keywords: GSM technology; IOT; Real Time; Trash; Waste management